Validitas Kelompok Minat Ilmu Psikis-Tes Minat Indonesia dengan TPA dan Sikap Terhadap Pelajaran - Jelpa Periantalo; Edi Saputra; Freddi Sarman (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2019)
AbstractThe purpose of this research was to get the support of the validity of the Indonesian Interest Tests through the components of interest in Psychic Sciences with variables whose measurements were valid. Psychic Interest consisted of sub-interests in the fields of Theology, Philosophy, Psychology, Education, Children with Special Needs and Management. The validity test was carried out with Academic Potential Tests and Attitudes towards the Study. The subjects of this study were Jambi University FKIK new students who received a Psychology test at the beginning of registration. There was no relationship between Psychic Interest and TPA with ρxy = -0.076 (p = 0.114; p <0.05; N = 479). There was a positive relationship with the attitude towards Sociology subject ρxy = 0.176 (p = 0.001; p <0.01; N = 470), and negative with Biology ρxy = -0.108 (p = 0.019; p <0.05; N = 470) there was no connection with other subjects. The Indonesian Interest Test was supported by various information about the validity of the construct through variables whose measurements are valid so that it had the power to diagose individual interests. TMI could be used for high school specialization, college majors, self career development, learning material, and research. To strengthen the validity it is recommended to test with academic achievement and learning satisfaction in the Psychology study program.AbstrakPenelitan  ini untuk mendapatkan dukungan validitas Tes Minat Indonesia melalui komponen minat Ilmu Psikis dengan variabel yang pengukuran sudah sahih. Minat Psikis terdiri dari sub minat di bidang Teologi, Filsafat, Psikologi, Pendidikan, Anak Berkebutuhan Khusus dan Manajemen. Uji validitias dilakukan dengan Tes Potensi Akademik dan Sikap terhadap Pelajaran. Subjek dari penelitian ini mahasiswa baru FKIK Universitas Jambi yang mendapatkan tes Psikologi diawal registrasi. Tidak ada hubungan antara Minat Psikis dengan TPA dengan ρxy = -0,076 (p=0,114; p <0,05; N=479). Terdapat hubungan positif dengan Sikap terhadap pelajaran Sosiologi  ρxy =0,176 (p=0,001; p<0,01; N=470), dan negatif dengan Biologi ρxy =-0,108 (p=0,019; p<0,05; N=470) tidak ada hubungan dengan pelajaran yang lain. Tes Minat Indonesia didukung berbagai informasi tentang validitas konstrak melalui variabel yang pengukuran sudah sahih sehingga memiliki kekuatan untuk mendiagosis minat individu. TMI dapat digunakan untuk peminatan SMA, penjurusan kuliah, penngembangan diri/karier, materi pembelajaran maupun penelitian. Untuk memperkuat validitas tersebut disarankan untuk uji dengan prestasi belajar maupun kepuasan belajar di program studi Psikologi.